2019
DOI: 10.3390/medicina55060290
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Overall Foot Health Questionnaire for Patients with Rheumatoid Arthritis: A Cross-Sectional Descriptive Analysis

Abstract: Background and Objectives: In general, patients with rheumatoid arthritis (RA) are ignorant of the physician’s role and of RA-related feet problems. The aim of our study was to validate a questionnaire on the knowledge of different aspects of overall foot health in patients with RA. Materials and Methods: A cross-sectional descriptive analysis was carried out between March 2017 and April 2017. A questionnaire was designed and validated through the Delphi method to evaluate the knowledge about the illness, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…A educação em saúde quando inserida no ambiente da escola pelo enfermeiro pode ser uma ferra- terminar o consenso entre os especialistas, adotando índice de concordância igual ou superior a 75%. (26,27) Após obtenção do IVC total de 85,7%, partiu-se para a avaliação das considerações e sugestões dos especialistas que foram acatadas na totalidade para melhora da linguagem da versão final da cartilha. É importante frisar que por meio das sugestões, essa cartilha foi desenvolvida observando as diferenças individuais das crianças de acordo com os cronótipos, que predispõem a uma preferência de horários para dormir e acordar, as fases de maior disposição física e cognitiva, respeitando a percepção individual dos ritmos circadianos e os sincronizadores externos em seres humanos.…”
Section: Discussionunclassified
“…A educação em saúde quando inserida no ambiente da escola pelo enfermeiro pode ser uma ferra- terminar o consenso entre os especialistas, adotando índice de concordância igual ou superior a 75%. (26,27) Após obtenção do IVC total de 85,7%, partiu-se para a avaliação das considerações e sugestões dos especialistas que foram acatadas na totalidade para melhora da linguagem da versão final da cartilha. É importante frisar que por meio das sugestões, essa cartilha foi desenvolvida observando as diferenças individuais das crianças de acordo com os cronótipos, que predispõem a uma preferência de horários para dormir e acordar, as fases de maior disposição física e cognitiva, respeitando a percepção individual dos ritmos circadianos e os sincronizadores externos em seres humanos.…”
Section: Discussionunclassified
“…Rheumatoid arthritis (RA) stands for an autoimmune disease caused by abnormal immune triggering that breaks tolerance against synovial antigens. RA is a chronic pathology characterized by synovial inflammation, joint pain, cartilage destruction, and bone erosion and damage-causing important deformation [ 112 , 113 ]. In RA, many studies have been carried out in an attempt to find the initial event that triggers immune dysregulation.…”
Section: The Interaction Between the Gut Microbiota And B Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…Moreover, podiatric intervention through therapeutic education of RA patients on the different potential foot problems could improve patients' knowledge and management of their foot problems. However, research describing foot‐related therapeutic education has been limited in RA patients (Reina‐Bueno et al., 2019). Previous studies have shown that RA patients have poor knowledge about RA‐related foot problems (A. S. Graham et al., 2017; Reina Bueno et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, research describing foot‐related therapeutic education has been limited in RA patients (Reina‐Bueno et al., 2019). Previous studies have shown that RA patients have poor knowledge about RA‐related foot problems (A. S. Graham et al., 2017; Reina Bueno et al., 2019). To give the patient clear and personally tailored information, it is essential to assess the knowledge that patients already have and its efficiency.…”
Section: Introductionmentioning
confidence: 99%